Hybrid AHP Topsis Method for Selection and the Four Disciplines of Execution (4DX) for Monitoring the Animal Disturbance Reduction Program (Case Study: PLN UP3 East Bali) - Mahardika, Kadek Eri; Irawan, Mohammad Isa (Syntax Literate, 2025)
PLN (Persero) East Bali Customer Service Implementation Unit is responsible for supplying electricity in Gianyar, Klungkung, Bangli, and Karangasem regencies. The high number of feeder disturbances, especially those caused by animals, significantly impacts the reliability and continuity of electricity supply, accounting for 115 incidents (37.33%) out of a total of 308 trips in the first semester of 2023. This study aims to determine the priority program for reducing animal-related disturbances using the hybrid Analytical Hierarchy Process (AHP) - Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method and to monitor its implementation using The Four Disciplines of Execution (4DX). The Delphi method established four evaluation criteria: ease of implementation, material cost, effectiveness, and power outage (KWH lost). Four alternatives were evaluated: installing palm fiber barriers, animal shields, heat shrink tubes, and tree pruning. The results indicated that tree pruning was the priority program. Implementation was monitored during the first semester of 2024 using the 4DX method, which showed a significant reduction in animal-related disturbances, decreasing from 115 incidents in the first semester of 2023 to 55 incidents in the first semester of 2024, representing a 52.21% year-over-year reduction. The implications of this study demonstrate that the hybrid AHP-TOPSIS and 4DX approaches effectively determine priorities and monitor program execution, significantly improving electricity supply reliability.